2019
DOI: 10.1049/iet-epa.2019.0060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of asymmetrical stator axes on the electromagnetic field and driving characteristics of canned induction motor

Abstract: Canned induction motors (CIMs) are particularly important for high vacuum application due to its low cost, simple design, and mechanically robust. Herein, this study reveals a mechanism of asymmetrical stator axes (ASAs) for CIMs and proposes six coefficients to describe ASA for CIMs under asymmetrical stator phase's windings. Using winding theorem, this study derived the electromagnetic field and driving characteristics in the healthy condition and ASA conditions for a 1.9 kW CIM, and analysed further using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Studies [13] showed that these parameters were higher for larger-capacity CMs. A 1.9 kW CM was, for instance, shown to have a locked rotor torque that was 92.2%, that of a same-sized IM [14]. Figure 4 shows typical NEMA design letter A or B torque-speed curves for an IM and the relative curve for a similar-sized CM, i.e., CM with lower LRT and BDT values.…”
Section: Motor Torque Characteristicsmentioning
confidence: 99%
“…Studies [13] showed that these parameters were higher for larger-capacity CMs. A 1.9 kW CM was, for instance, shown to have a locked rotor torque that was 92.2%, that of a same-sized IM [14]. Figure 4 shows typical NEMA design letter A or B torque-speed curves for an IM and the relative curve for a similar-sized CM, i.e., CM with lower LRT and BDT values.…”
Section: Motor Torque Characteristicsmentioning
confidence: 99%
“…To simplify the calculation, the electromagnetic field of the motor does not take into account the influence of the displacement current. The control equation and boundary condition of the transient electromagnetic field model are as follows [20]:}1em4pt x ν bold-italicA Z x + y )(ν A Z y = J Z + σ A Z t |A Z Γ = 0 where A Z is the magnetic vector potential, ν is the reluctivity, σ is the conductivity, J Z is the current density, and normalΓ is the outer boundary.…”
Section: Model Buildingmentioning
confidence: 99%
“…To simplify the calculation, the electromagnetic field of the motor does not take into account the influence of the displacement current. The control equation and boundary condition of the transient electromagnetic field model are as follows [20]:…”
Section: Prototype Parameters and The Finite Element Analysis Modelmentioning
confidence: 99%
“…Related to mechanical faults in the IM rolling bearing, massive approaches have been harnessed to diagnose rolling bearing failure, some techniques used are based on thermal analysis [17], vibration analysis [18], measurement and analysis of external magnetic field [19], sound-acoustic emission analysis [2], artificial intelligence analysis using various estimation methods [16].…”
Section: Introductionmentioning
confidence: 99%